Maternal Preeclampsia and Odds of Childhood Cancers in Offspring — A California Statewide Case-Control Study - Xu, Xiaoqing (Paediatr Perinat Epidemiol, 2017)
BACKGROUND: Preeclampsia is a major cause of adverse effects on fetal health. We examined associations between fetal exposure to preeclampsia and subsequent odds of childhood cancers. METHODS: We obtained childhood cancer cases (n=13,669) diagnosed at five years old or younger between 1988 and 2012 from the California Cancer Registry and linked them to birth certificates. Controls (n=271,383) were randomly selected from all California births and frequency matched to cases by birth year. We obtained data regarding preeclampsia during pregnancy, labour, and delivery from the medical worksheet of the electronic birth record. We used unconditional logistic regression models with stabilised inverse probability weights to estimate the effect of preeclampsia on each subtype of childhood cancer, taking into account potential confounding by pregnancy characteristics. Marginal structural models were fitted to assess the controlled direct effects of preeclampsia, independent of preterm delivery and NICU admission. RESULTS: Although a null association was observed for all cancer subtypes combined (odds ratio (OR) 1.0, 95% confidence interval (CI) 0.9, 1.2), preeclampsia was found to be associated with increased odds of two histologic subtypes of germ cell tumours: seminomas (OR 8.6, 95% CI 1.9, 38.4) and teratoma (OR 3.0, 95% CI 1.7, 5.4), but not yolk sac tumours in children. Odds remained elevated after adjusting for preterm delivery and NICU admission. Increases in odds were also observed for hepatoblastoma, however this association was attenuated in marginal structural models after accounting for NICU admission. CONCLUSIONS: These findings suggest that maternal preeclampsia is associated with higher odds of some rare childhood cancers and may shed light on new aetiologic factors for these cancers.